Missed nursing care and complexity theory: a conceptual paper. (December 2021) - Albsoul, Rania Ali; FitzGerald, Gerard; Hughes, James A; Ahmed Alshyyab, Muhammad
Background: Missed nursing care is a complex healthcare problem. Extant literature in this area identifies several interventions that can be used in acute hospital settings to minimise the impact of missed nursing care. However, controversy still exists as to the effectiveness of these interventions on reducing the occurrence of missed nursing care. Aim: This theoretical paper aimed to provide a conceptual understanding of missed nursing care using complexity theory. Methods: The method utilised for this paper is based on a literature review on missed care and complexity theory in healthcare. Results: We found that the key virtues of complexity theory relevant to the missed nursing care phenomenon were adaptation and self-organisation, non-linear interactions and history. It is suggested that the complex adaptive systems approach may be more useful for nurse managers to inform and prepare nurses to meet uncertain encounters in their everyday clinical practice and therefore reduce instances of missed care. Conclusions: This paper envisions that it is time that methods used to explore missed care changed. Strategies proposed in this paper may have an important impact on the ability of nursing staff to provide quality and innovative healthcare in the modern healthcare system.